Understanding How Big Data Technologies Reconfigure the Nature and Organization of Financial Statement Audits: A Sociomaterial Analysis. Issue 3 (27th May 2021) - Salijeni, George; Samsonova-Taddei, Anna; Turley, Stuart
ABSTRACT: This study focuses on the recent development in audit technologies, i.e., the rise of Big Data and Analytics (BDA) tools, and how auditors make use of them in audits. While prior audit studies have acknowledged that audit technologies shape and re-construct the market for audit services, they have not devoted much attention to the performative nature of such technologies and how their properties may shape the dynamics of technological change. Drawing on sociomateriality literature as well as observations, documentary materials and 25 semi-structured interviews with individuals directly engaging with BDA, this study explores how BDA users interact with particular properties of the technology in the course of an audit. We then consider how these interactions reconfigure aspects of the audit process and change the relational dynamics within audit firms. In particular, our findings suggest that properties of BDA such as scripts have afforded large-scale automation of audit routines, generating opportunities for expanding the evidential scope and depth of audit work. Further, we also show how the visualization dashboards have contributed to auditors' ability to communicate and justify their claims and judgements. Finally, we demonstrate that BDA has reshaped the nature of work relationships and flows between audit firms' different functions and service lines.